HOW IS IMPORTANT TO TEACH ESP (ENGLISH SPECIFIC PURPOSE) - Kasimov , Anvar Bahrom ugli (Educational Research in Universal Sciences, 2023)
The main aim of this article was to determine the importance of English Specific Purpose which not related English specific is used in real life. Furthermore it express the difficulties and how to solve them to learn language easily.